Moving beyond IPS: a person-centred approach to social inclusion and mental health - Anna Greenburgh; Mark Bertram; Helen Baldwin; Shaun Williams; Sarah McDonald; Craig Morgan (BJPsych Bulletin)
Many people experiencing mental ill health are trapped in cycles of worsening social exclusion. Individual Placement and Support (IPS) is being implemented to support those with mental ill health into employment. However, this intervention does not address the many challenges faced by those who are more vulnerable and is less effective for those with more severe clinical presentations. Although National Health Service (NHS) guidance suggests broader support is needed, there is little clarity over what this should look like. We discuss one model, drawing on years of experience facilitating user-led services at Lambeth Vocational Services, implementing a genuinely person-centred, trust-based approach to facilitate social inclusion.